2021
DOI: 10.1016/j.cortex.2021.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Characterising factors underlying praxis deficits in chronic left hemisphere stroke patients

Abstract: Limb apraxia, a disorder of skilled action not consequent on primary motor or sensory deficits, has traditionally been defined according to errors patients make on neuropsychological tasks. Previous models of the disorder have failed to provide a unified account of patients' deficits, due to heterogeneity in the patients and tasks used. In this study we implemented principal component analysis (PCA) to elucidate core factors of the disorder in a cohort of 41 unselected left hemisphere chronic stroke patients w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 145 publications
0
3
0
Order By: Relevance
“…103,132 More recent studies have used PCA to described apraxic deficits observed in patients. 105,134 In a preliminary study, 40 chronic stroke patients tested on 8 apraxia tasks, identified 2 core components underlying apraxia. 134 These involved action selection and semantic control.…”
Section: Challenges and Emerging Work Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…103,132 More recent studies have used PCA to described apraxic deficits observed in patients. 105,134 In a preliminary study, 40 chronic stroke patients tested on 8 apraxia tasks, identified 2 core components underlying apraxia. 134 These involved action selection and semantic control.…”
Section: Challenges and Emerging Work Diagnosismentioning
confidence: 99%
“…105,134 In a preliminary study, 40 chronic stroke patients tested on 8 apraxia tasks, identified 2 core components underlying apraxia. 134 These involved action selection and semantic control. The former was associated with lesions in the second branch of the superior longitudinal fasciculus, whereas the latter was associated with lesions within the ventral stream.…”
Section: Challenges and Emerging Workmentioning
confidence: 99%
“…To address this, a promising approach involves employing data-driven techniques like principal component analyses to unveil underlying, latent, patterns (Lambon Ralph et al, 2003, Butler et al, 2014. Notably, a prior study delved into apraxic de cits using principal component analyses, focusing on a set of eight apraxia tasks (Rounis et al, 2021). This analysis unveiled three core components that contributes to the disorder, encompassing aspects like posture selection, semantic control and sequencing de cits.…”
Section: Discussionmentioning
confidence: 99%